Weakly supervised salient object detection via double object proposals guidance. Issue 9 (4th March 2021) - Zhou, Zhiheng; Guo, Yongfan; Dai, Ming; Huang, Junchu; Li, Xiangwei
Abstract: The weakly supervised methods for salient object detection are attractive, since they greatly release the burden of annotating time‐consuming pixel‐wise masks. However, the image‐level annotations utilized by current weakly supervised salient object detection models are too weak to provide sufficient supervision for this dense prediction task. To this end, a weakly supervised salient object detection method is proposed via double object proposals guidance, which is generated under the supervision of double bounding boxes annotations. With the double object proposals, the authors' method is capable of capturing both accurate but incomplete salient foreground and background information, which contributes to generating saliency maps with uniformly highlighted saliency regions and effectively suppressed background. In addition, an unsupervised salient object segmentation method is proposed, taking advantage of the non‐parametric statistical active contour model (NSACM), for segmenting salient objects with complete and compact boundaries. Experiments on five benchmark datasets show that the authors' weakly supervised salient object detection approach consistently outperforms other weakly supervised and unsupervised methods by a considerable margin, and even has comparable performance to the fully supervised ones.